Malaria among young children in Twano-Papua: Evidence of determining factors in endemic areas - Ruth Yogi; Edison Kabak (Science Midwifery, 2023)
Malaria that occurs in children under 5 years has a high risk. Therefore, malaria control is made one of the main priorities in the health program by the Government. It is not yet known what the determining factors related to the incidence of young children in the Twano of Jayapura area. The objective is to identify the factors determinant associated with the incidence of malaria in young children (aged 0-5 years) in the working area of Twano of Jayapura. This study used a quantitative research with cross-sectional study. It was held in January 2021 with a sample size of 55 participated out of 61 people total samples. The inclusion criteria were mothers who had children aged 0-5 years. We used non-probability sampling technique. Data were obtained through questionnaires arranged according to the Likert Scale. Data were analyzed using SPSS version 25 with Chi-Square statistical test. The results showed three determinant factors associated with the incidence of malaria in children aged 0-5 years in Twano, Jayapura namely mothers' knowledge (p-value of 0.003), attitude (p-value of 0.005), and environment (p-value of 0.000). While the factors that were not associated with the incidence of malaria in children aged 0-5 years were education mothers (p-value of 0.318) and socioeconomic (p-value of 0.369). We found three important issues that influence the occurrence of malaria cases as determining factor in young children in Twano, Jayapura, namely knowledge, attitudes, and the environment. public health field practices based on the 2019 National Guidelines for HIV/AIDS Management.